2014
DOI: 10.2174/1874210601408010236
|View full text |Cite
|
Sign up to set email alerts
|

The True-Positive Rate of a Screening Questionnaire for Temporomandib-ular Disorders

Abstract: Background: Temporomandibular disorders (TMD) occur at an incidence of 5–12% in the general population. We aimed to investigate the rate of true-positives for a screening questionnaire for TMD (SQ-TMD) and differences in the characteristics between the true-positive and false-negative groups. Materials and Methods: Seventy-six individuals (16 men, 60 women; mean age, 41.1 ± 16.5 years) were selected from pa-tients with TMD who had visited the Temporomandibular Joint Clinic at Tokyo Medical and Dental Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Nishiyama et al . [ 13 ] showed that the true-positive rate of detecting TMD (based on the Research Diagnostic Criteria for TMD: RDC/TMD) using the SQ-TMD was very high (81.6%), and the SQ-TMD could be used to screen for TMD in patients with moderate or severe pain and difficulty completing activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Nishiyama et al . [ 13 ] showed that the true-positive rate of detecting TMD (based on the Research Diagnostic Criteria for TMD: RDC/TMD) using the SQ-TMD was very high (81.6%), and the SQ-TMD could be used to screen for TMD in patients with moderate or severe pain and difficulty completing activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements VAS: visual analogue scale. A graphic representation of a patient's face where they had to highlight painful areas, specifying the intensity (from 0 = No Pain to 10 = Maximum Pain) and occurrence of the disturbance [37].…”
Section: Methodsmentioning
confidence: 99%
“…VAS: visual analogue scale (VAS); it is a graphical representation where the subject has to highlight painful areas, specifying the severity (value from 0 to 10) and the disturbance frequency [20].…”
Section: Measurementsmentioning
confidence: 99%